Zanzibar: Re-Searching the “Other Andalus” - Ghazal, Amal N. (al-Akhbar, 2013)
Keywords: Zanzibar

From Siraf to Sumatra: Seafaring and Spices in the Islamicate Indo-Pacific, Ninth-Eleventh Centuries C.E. - Averbuch, Brian (Harvard University, 2013)
Keywords: Zanzibar

The Threat of Liberation: Imperialism and Revolution in Zanzibar - Wilson, Amrit (Pluto Press, 2013)
The Threat of Liberation returns to the tumultuous years of the Cold War, when, in a striking parallel with today, imperialist powers were seeking to institute ‘regime change’ and install pliant governments.Using iconic photographs, declassified US and British documents, and in-depth interviews, Amrit Wilson examines the role of the Umma Party of Zanzibar and its leader, the visionary Marxist revolutionary, Abdulrahman Mohamed Babu. Drawing parallels between US paranoia about Chinese Communist influence in the 1960s with contemporary fears about Chinese influence, it looks at the new race for Africa’s resources, the creation of AFRICOM and how East African politicians have bolstered US control. The book also draws on US cables released by Wikileaks showing Zanzibar's role in the ‘War on Terror’ in Eastern Africa today.The Threat of Liberation reflects on the history of a party which confronted imperialism and built unity across ethnic divisions, and considers the contemporary relevance of such strategies.
Keywords: Zanzibar